Rational Modelling to Support Stunting Diagnosis Rational Modelling to Support Stunting Diagnosis - Masrochah, Siti; Darmini, Darmini; Sari, Yeti Kartika; Susanto, Edy (Poltekkes Kemenkes Semarang, 2024)
Stunting is a health problem characterized by disrupted growth conditions in toddlers due to a lack of nutritional intake over a long period of time, starting in the womb until the child is two years old. Stunting causes children to be short in stature and is at risk of causing problems with motor and mental development. In Cilacap Regency, the prevalence of stunting reached 32.1%, above the national figure and the limit set by WHO. Therefore, accelerating stunting reduction is carried out through a holistic, integrative and multisector approach. One of the efforts made is the development of an information system to comprehensively monitor and prevent stunting, including a diagnostic model that involves various health parameters.